2021
DOI: 10.3390/f12091204
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Methane in Mangrove Forest: Will It Worsen with Decreasing Mangrove Forests?

Abstract: Mangrove forests sequester a significant amount of organic matter in their sediment and are recognized as an important carbon storage source (i.e., blue carbon, including in seagrass ecosystems and other coastal wetlands). The methane-producing archaea in anaerobic sediments releases methane, a greenhouse gas species. The contribution to total greenhouse gas emissions from mangrove ecosystems remains controversial. However, the intensity CH4 emissions from anaerobic mangrove sediment is known to be sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 121 publications
(219 reference statements)
0
3
0
Order By: Relevance
“…The discrepancy between high relative abundances of methanogenic archaea communities and low porewater CH 4 concentrations at this site suggests the possibility of either low overall activity of the methanogen communities at the time of sampling due to seasonality and physicochemistry; CH 4 translocation elsewhere; and/or limited data from deeper sediment skewing relative abundances. The findings also underpin the importance of coastal vegetation such as mangrove forests (Sippo et al 2018; Arai et al 2021). Here, we show that these forests are confining methanogenesis to deeper layers within and potentially below the rhizosphere, likely via vertical nutrient distributions and competition with other microorganisms, such as an abundance of sulfate reducers within the rhizosphere.…”
Section: Discussionmentioning
confidence: 79%
“…The discrepancy between high relative abundances of methanogenic archaea communities and low porewater CH 4 concentrations at this site suggests the possibility of either low overall activity of the methanogen communities at the time of sampling due to seasonality and physicochemistry; CH 4 translocation elsewhere; and/or limited data from deeper sediment skewing relative abundances. The findings also underpin the importance of coastal vegetation such as mangrove forests (Sippo et al 2018; Arai et al 2021). Here, we show that these forests are confining methanogenesis to deeper layers within and potentially below the rhizosphere, likely via vertical nutrient distributions and competition with other microorganisms, such as an abundance of sulfate reducers within the rhizosphere.…”
Section: Discussionmentioning
confidence: 79%
“…Water flow influences nutrient run-off and aquaculture activity positively influences soil CH 4 effluxes (Zheng et al, 2018). Besides anthropogenic activity, Arai et al (2021) found other factors such as soil condition, methanogens (i.e., CH 4 -producing microorganisms), methanotroph (i.e., CH 4 -oxidizing microorganisms), and mangrove species also affected CH 4 emissions.…”
Section: Effect Of Mangrove Conversion On Carbon Effluxesmentioning
confidence: 91%
“…Topic II: Blue carbon ecosystem assessment and sustainable management Seagrasses (dead seagrass, seagrass beds, seagrass meadows), mangroves, coral reefs, kelps, saltmarshes, macroalgae (or seaweeds), benthic microalgae, etc., constitute the blue carbon ecosystem, whose comprehensive benefit is also determined by the size, quality, and extent of the ecosystem [69,71,76,104,110,124,135,136,161,164,165,168,[170][171][172][173][174][175][176][177][178][179][180][181][182][183][184]. Due to the structural complexity of coastal vegetation ecosystems (root systems, dense vegetation, and leafy canopy in seagrass systems), salt marshes, mangroves, and seagrass beds are capable of efficiently capturing sediment and associated organic carbon from both riverine and oceanic sources [164].…”
Section: Currently Researched Topicsmentioning
confidence: 99%